A prospective study of tracheopulmonary complications associated with the placement of narrow-bore enteral feeding tubes - Rassias, Athos J (BioMed Central, 1998)
BACKGROUND: In order to determine the type and incidence of pulmonary complications associated with the placement of narrow-bore enteral feeding tubes we conducted a prospective, descriptive study in the multidisciplinary intensive care unit (ICU) of a university hospital. All patients that had narrow-bore enteral feeding tubes inserted over a 2-year period (1993-1995) were included. The study required no clinical interventions. RESULTS: Seven hundred and forty feeding tubes were inserted during the study period. In 14 cases (2%), the feeding tube was inserted into the tracheopulmonary system. Five patients (0.7%) suffered a major complication, including two (0.3%) who died from complications directly related to the feeding tube placement. All patients had altered consciousness and 13 of the 14 had endotracheal tubes in place. Malposition of the feeding tube was not predictable from clinical signs and auscultation, but was detectable by chest roentgenogram. CONCLUSIONS: Inadvertent insertion of enteral feeding tubes into the tracheopulmonary system during placement is associated with significant morbidity and mortality. Clinical signs at the time of insertion are not useful in identifying feeding tubes which are malpositioned. In the ICU patient, a chest roentgenogram is required after all feeding tube insertions prior to the initiation of enteral feeding. In the high-risk patient, alternatives to blind feeding tube insertion should be considered.